Nootkatol prevents ultraviolet radiation-induced photoaging via ORAI1 and TRPV1 inhibition in melanocytes and keratinocytes - Woo, Joo Han; Nam, Da Yeong; Kim, Hyun Jong; Hong, Phan Thi Lam; Kim, Woo Kyung; Nam, Joo Hyun (The Korean journal of physiology & pharmacology, 2021)
Skin photoaging occurs due to chronic exposure to solar ultraviolet radiation (UV), the main factor contributing to extrinsic skin aging. Clinical signs of photoaging include the formation of deep, coarse skin wrinkles and hyperpigmentation. Although melanogenesis and skin wrinkling occur in different skin cells and have different underlying mechanisms, their initiation involves intracellular calcium signaling via calcium ion channels. The ORAI1 channel initiates melanogenesis in melanocytes, and the TRPV1 channel initiates MMP-1 production in keratinocytes in response to UV stimulation. We aimed to develop a drug that may simultaneously inhibit ORAI1 and TRPV1 activity to help prevent photoaging. We synthesized nootkatol, a chemical derivative of valencene. TRPV1 and ORAI1 activities were measured using the whole-cell patch-clamp technique. Intracellular calcium concentration [Ca ]i was measured using calcium-sensitive fluorescent dye (Fura-2 AM). UV-induced melanin formation and MMP-1 production were quantified in B16F10 melanoma cells and HaCaT cells, respectively. Our results indicate that nootkatol (90 μM) reduced TRPV1 current by 94% ± 2% at -60 mV and ORAI1 current by 97% ± 1% at -120 mV. Intracellular calcium signaling was significantly inhibited by nootkatol in response to ORAI1 activation in human primary melanocytes (51.6% ± 0.98% at 100 μM). Additionally, UV-induced melanin synthesis was reduced by 76.38% ± 5.90% in B16F10 melanoma cells, and UV-induced MMP-1 production was reduced by 59.33% ± 1.49% in HaCaT cells. In conclusion, nootkatol inhibits both TRPV1 and ORAI1 to prevent photoaging, and targeting ion channels may be a promising strategy for preventing photoaging.